Pendidikan Musik Berbasis Komunitas: Pendekatan Sekolah Alam untuk Pemberdayaan Anak Jalanan di Bandung - Ayusita Leonisfata Nursidqiyah; Sandie Gunara (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: This article aims to describe the learning experience and determine the effectiveness of informal music education through nature classes conducted by Komunitas Musik Untuk Langit (KML) Bandung as an alternative education for street children and middle to lower economic communities amid the high cost of formal education, focusing on the learning experience and the resulting social impact on community members and society. Method: this research uses a descriptive qualitative method, data is collected through observation in the form of field research by interviews with community members, documentation and digital archives. Results and Discussion: the research includes a brief history of KML, the application of informal music education by KML which uses the concept of natural schools by utilizing natural open spaces as classes, in the process KML applies three learning models: a). discovery learning, b). experiential learning and c). cognitive learning, in addition to developing the potential for creativity in music, moral education and manners related to ethics and religious values are also carried out, as well as connecting them with elements of creativity which include; human resources, non-human resources and the results achieved. Conclusion: The results of this study indicate that informal music education organized by KML has succeeded in having a positive impact on street children by becoming a forum for those who are less capable so that they can learn and develop their creative potential in music, moral and manners provision is able to reduce the negative stigma of street children and increase public confidence in accepting their presence.